Trabalho em ambiente metaverso: aplicação dos direitos fundamentais à luz do pós-positivismo jurídico conferindo tratamento efetivo ao princípio constitucional da dignidade da pessoa humana - Santos, Ariane Joice dos (2023)
This thesis intends to investigate whether work in a metaverse environment, a consequence of the development of crafts in an exclusively digital and fully immersive environment with augmented and three-dimensional reality, is a disruptive modality of labor law or if the observance of fundamental rights is necessary in this new work relationship, as well as the constitutionalization of law, with regard to the core of human dignity